Frequent wheeze at follow up of very preterm infants: which factors are predictive?. Issue 4 (1st July 2003) - Thomas, M; Greenough, A; Johnson, A; Limb, E; Marlow, N; Peacock, J L; Calvert, S
Abstract : Objective: To determine if chest radiograph appearance at 28 days or 36 weeks postmenstrual age (PMA) can predict recurrent wheeze or cough at follow up in prematurely born infants more effectively than readily available clinical data. Design: Chest radiographs of infants entered into the UKOS trial, who had had a chest radiograph at 28 days and 36 weeks PMA and completed six months of follow up, were assessed for the presence of fibrosis, interstitial shadows, cystic elements, and hyperinflation. At 6 months of corrected age, the occurrence and frequency of wheeze and cough since discharge were determined using a symptom questionnaire. Patients: A total of 185 infants with a median gestational age of 26 (range 23–28) weeks. Results: Thirty seven infants wheezed more than once a week, compared with the rest of the cohort. These infants had significantly higher chest radiograph scores at 28 days (p = 0.020) and 36 weeks PMA (p = 0.005), with significantly higher scores at 28 days for fibrosis (p = 0.017) and at 36 weeks PMA for fibrosis (p = 0.001) and cystic elements (p = 0.0007). They had also been ventilated for longer (p = 0.013). Forty four infants coughed more than once a week; they did not differ significantly from the rest of the cohort. An abnormal chest radiograph score at 36 weeks PMA had the largest area under the receiver operator characteristic curve with regard to prediction of frequent wheeze. Conclusion: An abnormal chest radiograph appearance at 36 weeks PMA predicts frequent wheeze at follow up and appears to be a better predictor than readily available clinical data.